Liability of civil servants - Buzescu, Gheorghe (Eximia, 2024)
This study of the liability of civil servants aims to analyze the applicable regulations and principles in order to clarify the notions that constitute this system for the proper performance of public administration activities, as well as the appropriate behavior of those administered. Public administration, from a material point of view, is achieved through a multitude of organizational forms, which make up the public administration system. This system is linked, functionally and organizationally, to the legislative power and the executive power. As an activity, public administration represents the organization of the execution and execution of the law in the most diverse areas of social action and in relation to certain human communities that make up the global social system. The main purpose of this paper is to present and analyze the civil, criminal and administrative liability of public officials, as forms of legal liability and, in the alternative, to establish the limits of this liability. The topicality of the legislation in the field makes the research topic conditioned by the need to study and analyze in detail the existing national normative framework. For a more rigorous regulation and in correlation with the obligations assumed towards the European Union institutions, Romania adopts the Administrative Code in 2019. I also emphasize that the information is updated until the moment of completion of the writing of the paper, being exposed according to the available information. From the point of view of the chronological framework, the work focuses on a long period of time, from the emergence of the concept of public function and the notion of civil servant to the present day. Analysing, we can say that this institution has hardly been outlined in the Romanian literature, the opinions expressed in the specialized doctrine being diversified, from the justification of its presence, to the contestation of the existence of the types of liability or the applicable legal regulations.